(untitled) (Journal of Naval Architecture and Marine Engineering, 2024)
A three-dimensional thermal-electric including a four-tiny radiofrequency probe, hepatic tissue, and an integrated model of a large blood vessel are investigated numerically. The FEM is employed in the determination of the distribution of tissue temperature during radiofrequency hepatic tumor ablation through the heated targeted cells that are supposed to kill and the healthy surrounding tissues are supposed to save. The mathematical reproduction is led for various times from 0 s to 1000 s and electric voltage from 22 V to 50 V with good convergence of the iterative scheme. In terms of temperature fields at different times, iso-surfaces with temperatures of 50°C at various times, iso-surfaces at different temperatures, and the temperature distribution over time are displayed graphically. Temperature distribution against time at the tip of one of the electrodes arms at a fixed voltage and various voltages are also demonstrated. Results from the RF simulation specify that temperature increases due to increasing time of ablation of tumor and electric voltage. The tumor cell is killed approximately at 50°C with 22 V after 480 s heating. The proposed model may be a new tool for physicians for the efficient thermal insulation of tumors without any significant damage in healthy tissues. Journal of Naval Architecture and Marine Engineering, 21 (1), 2024, pp. 51–66